Magneto-luminescence of quasi-zero dimensional In0.25Ga0.75As/GaAs quantum dots - Cheng, H; Nicholas, R; Priest, A; Tsai, F; Lee, C; Sanchez-Dehesa, J (1998)
We report photoluminescence measurements on In0.25Ga0.75As/GaAs quantum well and dots grown on (1 1 1)B GaAs substrate in high magnetic fields up to 45 Tesla. A well-defined PL line with full width at half maximum of approximately 5.5 meV is observed. From an analysis of the zero field transition energy, we point out the importance of an internal piezoelectric field. By analyzing the diamagnetic shift of the PL in both Faraday and Voigt configurations, the optical characteristics of a quasi-zero dimensional exciton are discussed. (C) 1998 Elsevier Science B.V. All rights reserved.